Operasional Ritel Indomaret di Kecamatan Rumbai Kota Pekanbaru Berdasarkan Peraturan Daerah No. 9 Tahun 2014 tentang Pengelolaan Pusat Perbelanjaan dan Toko Swalayan - Andre Gusto Sihite; Yalid (Jurnal Hukum Respublica, 2018)
The purpose of this study was conducted: First, to explain the retail operating hours of Indomaret in Rumbai District, Pekanbaru City. Second, to analyze the constraints of Indomaret’s retail operating hours in Rumbai District, Pekanbaru City. Third, to explain how to overcome the constraints of Indomaret’s retail operating hours in Rumbai District, Pekanbaru City. The type of sociological legal research, according to its type, empirical approach emphasizes the effectiveness of law. The results of this study can be explained that the retail operations of Indomaret in the District of Rumbai in Pekanbaru City are carried out through a sanction mechanism, beginning with a written warning, followed by the freezing of business licenses, to sanctions closing business licenses. The constraints of Indomaret’s retail operating hours in Rumbai District in Pekanbaru City are due to human resource factors, the lack of synchronization between related agencies and ignorance of the prevailing laws and regulations so that the lack of awareness of business actors in Rumbai District in Pekanbaru City. Efforts to curb Indomaret’s retail operating hours in the Rumbai District of Pekanbaru, in the form of socialization regarding the laws and regulations that apply to the awareness of business actors and the public. In this regard, many business operators in Rumbai District do not know that Indomaret retails should have limited operating hours in accordance with Bylaw No. 9 of 2014. This was obtained based on facts from interviews with relevant respondents.